Strategies for the Contextualization of Religious Content Through Social Media for STKIP Students - Suhaili, Hidayati; Kustati, Martin; Amelia, Rezki; Sartini, Titi; Nini, Nini (Jurnal Kajian dan Pengembangan Umat, 2025)
This study aims to examine the contextualization strategy of religious content by STKIP Abdi Pendidikan Payakumbuh students through social media in order to strengthen understanding and internalization of moderate and contextual Islamic values. This research uses a qualitative approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. The results showed that students not only act as passive consumers, but also as active, adaptive, and reflective producers of religious content. Contextualization strategies are carried out through the use of communicative and dialogical language, the selection of visual formats that are attractive and in accordance with the characteristics of digital platforms, and the delivery of Islamic values that are reflective, moderate, and relevant to contemporary issues. However, this process is not free from various challenges, such as limited digital and religious literacy, time constraints, algorithmic pressure, and social resistance in the form of negative comments. This research recommends the importance of strengthening digital Islamic literacy, creative media training, and the integration of digital da'wah in student character development programs in higher education.